Boosting the performance and stability of inverted perovskite solar cells by using a carbolong derivative to modulate the cathode interface. (13th July 2022) - Li, Jinhua; Wang, Jiantao; Zhou, Yecheng; Yu, Chengzhuo; Liu, Heng; Qi, Xingnan; Li, Ruxue; Hua, Yuhui; Yu, Yinye; Chen, Rui; Chen, Dafa; Mao, Lingling; et al.
Abstract : A carbolong derivative with a M-PCCO framework was employed as the cathode interlayer, boosting the performance and stability of inverted PSCs. Abstract : Perovskite solar cells (PSCs) require low work function (WF) cathodes to collect electrons, but often chemically reactive metals are used for devices with inverted configuration. Reactive metals (such as Ag, Cu and Al) with low WF encounter easy oxidation and corrosion, which threatens the long-term stability of devices. Herein, we tailor an organometallic carbolong derivative to modulate the cathode interface in inverted PSCs for the enhancement of power conversion efficiency (PCE) and stability. Density functional theory and surface WF characterization reveal that this organometallic compound can reduce the WF of metals by forming interfacial and molecular dipoles, which reduce the energy barrier for electron transport from the electron transport layer to the external metal cathode. By using this carbolong derivative to modulate the cathode interface, inverted PSCs based on the commonly used Ag cathode obtain a PCE of 21.46% with a remarkable FF of 83.14%. By replacing low-WF Ag with high WF Au, the devices achieve more than 20% PCE and improved ambient stability, and can maintain over 85% of the initial PCE for over 500 h in an inert environment under the maximum power point (MPP) tracking. This work provides a significant route for the realization of high-efficiency and stable PSCs by integrating rationally designed cathode interfacial materials and chemically stable metals.